Cases of Absolute and Relative Nullity regarding the Institution of Marriage - Niculescu, Liliana (Acta Universitatis Danubius. Juridica, 2022)
Considering the indisputable importance of marriage at the individual and social level, it is necessary that it benefits from a legal framework that gives it protection and stability. The Romanian legislator provided by imperative provisions the substantive and formal conditions for the conclusion of marriage. But, despite all the preventive measures taken by the legislator and the right of the registrar to refuse to celebrate the marriage, when one or more conditions are not met, situations may arise in which the marriage is void or voidable. Thus, the legislator did not exclude the possibility of violating the requirements of the law for one reason or another. For this reason, considering the real interest that the legal institution of marriage nullity generates, in this article, based on the legislation in force I proposed to address the doctrinal guidelines, after a short introductory part in which they are put in discussion of general aspects regarding marriage and its nullity, cases of absolute nullity, respectively, cases of relative nullity of marriage. This work was supported by a financing agreement concluded with the „Dunărea de Jos” University from Galati, no. 14713/10.05.2022. Paper published within Internal Research Project based on the Financial Contract with „Dunărea de Jos” University of Galaţi/Contract de finanţare cu Universitatea „Dunărea de Jos” din Galaţi, nr. 14713/10.05.2022.14thInternational Conference “Exploration, Education and Progress In The Third Millennium” 12-13th May 2022, https://www.fdsa.ugal.ro/images/2022/Conferinte/Book_of_Abstracts_EEP_Conference_2022_compressed.pdf